Real-World Efficacy and Safety of Ritonavir-Boosted Paritaprevir, Ombitasvir, Dasabuvir ± Ribavirin for Hepatitis C Genotype 1 – Final Results of the REV1TAL Study. Issue 8 (November 2017) - ,; Lubel, John; Strasser, Simone; Stuart, Katherine A; Dore, Gregory; Thompson, Alexander; Pianko, Stephen; Bollipo, Steven; Mitchell, Joanne L; Fragomeli, Vincenzo; Jones, Tracey; Chivers, Sarah; et al.
Background: Limited data exist on the outcomes of ritonavir-boosted paritaprevir with ombitasvir and dasabuvir (PrOD) ± ribavirin in a real-world setting. The aim of this study was to compare the efficacy and safety of PrOD-based therapy in hepatitis C genotype 1 patients with and without cirrhosis, and to explore pre-treatment factors predictive of sustained viral response (SVR) and serious adverse events (SAEs) on treatment. Methods: 451 patients with hepatitis C genotype 1 treated in 20 centres across Australia were included. Baseline demographic, clinical and laboratory information, on-treatment biochemical, virological and haematological indices and details on serious adverse events were collected locally. Results: Cirrhosis was present in 340 patients (75.4%). Overall SVR was 95.1% with no differences in SVR between the cirrhosis and non-cirrhosis groups (94.7% versus 96.4%). SVR in subgenotypes 1a and 1b was 93.1% and 99.2%, respectively. On multivariate analysis, baseline bilirubin level and early treatment cessation predicted SVR. SAEs occurred in 10.9% of patients including hepatic decompensation (2.7%) and hepatocellular carcinoma (1.8%). On multivariate analysis of factors predictive of SAEs in the overall group, Child-Turcotte-Pugh (CTP) B was the only significant factor, while in those with cirrhosis, baseline albumin and creatinine levels were significant. Conclusions: In this large real-world cohort of HCV genotype 1 subjects, treatment with PrOD was highly effective and similar to clinical trials. Important determinants of reduced SVR include early cessation of therapy and baseline bilirubin concentration. SAEs were not infrequent with CTP B patients being at greatest risk.